Sociodemographic and Clinical Factors Affecting Treatment Adherence in Adults with Attention Deficit and Hyperactivity Disorder - ERKAN, ARZU; Kılıç, Özge; Semerci, Bengi (Aves, 2022)
Background: This study aims to explore sociodemographic and clinical factors affecting medication adherence in adults with attention deficit and hyperactivity disorder and elicit dysfunctional domains and comorbidities with a focus on gender differences. Methods: Patients were recruited from 2 specialty clinics using chart records in a natural treatment design. Adult attention deficit and hyperactivity disorder self-report scale, Diagnostic Interview for attention deficit and hyperactivity disorder in adults, was applied. Adherence is defined if the patient declared >= 80% adherence to medication throughout the last 8-12 weeks. Results: From 205 attention deficit and hyperactivity disorder patients (male =112 female = 93 (age (median) min-max = 29 (18-56)), 29% were non-adherent to attention deficit and hyperactivity disorder medication. In the multivariate analysis, having 2 or more comorbid disorders (P = .009), dysfunctions in academic/work (P= .049), and dysfunctions in family and other relationships (P = .047) increased the likelihood of adherence. Adherence rates did not significantly differ between methylphenidate and atomoxetine (P= .405). Women were more likely to have 2 or more comorbid psychiatric disorders (P = .004) and dysfunctions in social relationships (P= .001), free time activities, hobbies (P < .001), self-confidence, and self-image (P < .001). Results: Nearly one-third of adult patients with attention deficit and hyperactivity disorder did not adhere to medication treatment. Comorbid psychiatric disorders and dysfunctions in life domains appear to increase the likelihood of adherence to attention deficit and hyperactivity disorder medications, possibly through increasing motivation for treatment. The effect of cognitive-behavioral therapy on compliance with attention deficit and hyperactivity disorder medication should further be explored with prospective controlled studies. Conclusion: We suggest that future longitudinal studies use objective measures of adherence and confirm the role of dysfunctional life domains and comorbid psychiatric disorders as correlates of medication adherence.
Keywords: Attention Deficit Hyperactivity Disorder; Cognitive Behavioral Therapy; Drugs/Medication; Pharmacology; Treatment Compliance